Developing cash waqf model as an alternative source of financing for micro enterprises in Malaysia - Mohd Thas Thaker, Mohamed Asmy; Mohammed, Mustafa Omar; Duasa, Jarita; Abdullah, Moha Asri (Emerald Group Publishing Ltd., 2016)
Purpose – This paper aims to attempt to offer a viable alternativemodel of source of financing whichis known as integrated cash waqf micro enterprises investment (ICWME-I) model for micro enterprises in Malaysia. Design/methodology/approach – The literature on the issues of accessing to finance faced by micro enterprises and cash waqf are reviewed critically and used in the attempt of proposing an alternative model. Findings – The paper has developed ICWME-I model as a source of financing for micro enterprises. This model is expected to provide financial services by using cash waqf fund and involved the participatory contract between non-profit organization and micro enterprises. In addition, with the proposed model, there will be no collateral requirement, interest rate and other stringent requirements which usually imposed by existing conventional financial institutions. Research limitations/implications – The paper is based on conceptual explorations of literature in the area of micro enterprises and cash waqf. This is a conceptual paper, so it did not use any empirical analysis. Practical implications – The findings of this paper will provide micro enterprises with an alternative source of financing to start-up or expand their business by using cash waqf fund. The present study also has implications for government and policy makers. With the involvement of non-profit organization that is proposed in this model, it helps the government to reduce its expenses for the development of micro enterprises. Originality/value – This paper offers an additional literature on cash waqf especially from the Malaysian context. Furthermore, this paper adds to the literature on waqf and cash waqf. The paper proposes a viable alternative model for micro enterprises as a source of financing by using cash waqf fund. This model incorporates Musharakah Mutanaqisah (diminishing partnership) as a financial arrangement between non-profit organization and micro enterprises